A novel anti-tumor inhibitor identified by virtual screen with PLK1 structure and zebrafish assay. - Jing Lu; Shengchang Xin; Huan Meng; Matt Veldman; David Schoenfeld; Chao Che; Ruibin Yan; Hanbing Zhong; Song Li; Shuo Lin (PLoS ONE)
Polo-like kinase 1 (PLK1), one of the key regulators of mitosis, is a target for cancer therapy due to its abnormally high activity in several tumors. Plk1 is highly conserved and shares a nearly identical 3-D structure between zebrafish and humans. The initial 10 mitoses of zebrafish embryonic cleavages occur every∼30 minutes, and therefore provide a rapid assay to evaluate mitosis inhibitors including those targeting Plk1. To increase efficiency and specificity, we first performed a computational virtual screen of∼60000 compounds against the human Plk1 3-D structure docked to both its kinase and Polo box domain. 370 candidates with the top free-energy scores were subjected to zebrafish assay and 3 were shown to inhibit cell division. Compared to general screen for compounds inhibiting zebrafish embryonic cleavage, computation increased the efficiency by 11 folds. One of the 3 compounds, named I2, was further demonstrated to effectively inhibit multiple tumor cell proliferation in vitro and PC3 prostate cancer growth in Xenograft mouse model in vivo. Furthermore, I2 inhibited Plk1 enzyme activity in a dose dependent manner. The IC50 values of I2 in these assays are compatible to those of ON-01910, a Plk1 inhibitor currently in Phase III clinic trials. Our studies demonstrate that zebrafish assays coupled with computational screening significantly improves the efficiency of identifying specific regulators of biological targets. The PLK1 inhibitor I2, and its analogs, may have potential in cancer therapeutics.